1994
DOI: 10.1152/jappl.1994.77.2.684
|View full text |Cite
|
Sign up to set email alerts
|

Higher exercise performance and lower VO2max in Tibetan than Han residents at 4,700 m altitude

Abstract: To examine the hypothesis that the pathway of adaptation to high altitude in natives differs considerably from that in newcomers, we measured maximal O2 uptake (VO2max), minute ventilation, anaerobic threshold (AT), blood lactate, and blood gases during maximal exercise in 17 lifelong Tibetan residents and 14 acclimatized Han Chinese newcomers living at the altitude of 4,700 m. The two groups were similar in age, height, and weight, and the subjects were nonathletes. Although VO2max was significantly lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 0 publications
3
49
0
Order By: Relevance
“…In contrast, both Sherpas and Andean Quechuas show evidence for enhanced cardiac glucose uptake at the tissue level (50), and in Sherpas, the decreased ratio of phosphocreatine to ATP in cardiac myocytes suggests a greater reliance on glucose for ATP production (51). However, neither Quechuas nor Sherpas exhibit enhanced maximal aerobic capacities compared with lowlanders at similar fitness levels (52,53), suggesting that human patterns of metabolic adjustment may be optimized to enhance O 2 economy rather than maximal aerobic capacity (54).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both Sherpas and Andean Quechuas show evidence for enhanced cardiac glucose uptake at the tissue level (50), and in Sherpas, the decreased ratio of phosphocreatine to ATP in cardiac myocytes suggests a greater reliance on glucose for ATP production (51). However, neither Quechuas nor Sherpas exhibit enhanced maximal aerobic capacities compared with lowlanders at similar fitness levels (52,53), suggesting that human patterns of metabolic adjustment may be optimized to enhance O 2 economy rather than maximal aerobic capacity (54).…”
Section: Discussionmentioning
confidence: 99%
“…After resting 30 min while seated, subjects performed the exercise test on an electronically braked cycle ergometer (Ergo-Oxyscreen, Jaeger, Wü rzburg, Germany), as previously described (12) to estimate V O 2 max , which is equivalent to V O 2 max at a steady-state condition, at a maximal exercise condition. The gas analyzers were calibrated before each measurement of expired gas by using ambient air and a gas mixture of 15% O 2 -5% CO 2 -80% N 2 that had been previously measured by using the Scholander technique.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the reduction of ambient O 2 pressure at high altitude. Although comparative studies of V O 2 max between high altitude natives and lowland residents at high-altitude have been done, the conclusions are controversial (10)(11)(12)(13)30). High-altitude adult natives in either Andean or Himalayan populations have higher exercise performance and maintain better arterial O 2 saturation (Sa O 2 ) during exercise compared with newcomers (17,20,30,38).…”
mentioning
confidence: 99%
“…9 Another study concluded that Tibetans born at low altitude do not seem to differ from lowlanders with regard to their metabolic response whereas their ventilatory response to exercise is greater. 10 Hence we conclude in our study that, though both Indian born Tibetan male youths and Indian male youths share similar environmental challenges, this difference in PEFR and MVV has shown that Indian born Tibetan male youths have retained better respiratory parameters as their ancestors which could be due to their inheritance of genetic factors which favour the Tibetans to survive at high altitude.…”
Section: Discussionmentioning
confidence: 52%